Association study between the rs165599 catechol-O-methyltransferase genetic polymorphism and schizophrenia in a Brazilian sample - Quirino Cordeiro; Renata Teixeira da Silva; Homero Vallada (Arquivos de Neuro-Psiquiatria)
Schizophrenia is a severe psychiatric disorder with frequent recurrent psychotic relapses and progressive functional impairment. It results from a poorly understood gene-environment interaction. The gene encoding catechol-O-methyltransferase (COMT) is a likely candidate for schizophrenia. Its rs165599 (A/G) polymorphism has been shown to be associated with alteration of COMT gene expression. Therefore, the present study aimed to investigate a possible association between schizophrenia and this polymorphism. The distribution of the alleles and genotypes of this polymorphism was investigated in a Brazilian sample of 245 patients and 834 controls. The genotypic frequencies were in Hardy-Weinberg equilibrium and no statistically significant differences were found between cases and controls when analyzed according to gender or schizophrenia subtypes. There was also no difference in homozygosis between cases and controls. Thus, in the sample studied, there was no evidence of any association between schizophrenia and rs165599 (A/G) polymorphism in the non-coding region 3' of the COMT gene.